2016
DOI: 10.1111/1745-8315.12403
|View full text |Cite
|
Sign up to set email alerts
|

Psychic reality and the nature of consciousness

Abstract: In this paper we make the case for a psychoanalytically informed reconsideration of the phenomena of consciousness. Classically, following Freud, who viewed consciousness as merely a reflection or perception of unconscious mental activity, psychoanalysts have tended to regard a focus on conscious experience as potentially reductionistic and at risk of overlooking the mind's deeper structures. We describe the case of Mr K, a patient who experienced disturbances of consciousness that forced us to consider the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…These are key elements that enable the social cooperation, social learning and the construction of a network of relationships that make culture and its transmission possible [6]. We have argued, in a similar vein, that human consciousness evolved to allow us to share our experiences, to communicate a "shared narrative" on which relationships, social ties, and group cohesion can all be built [7]. We become conscious of those aspects of the world which others reflect on as well, and this applies equally to our internal subjective world [7].…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…These are key elements that enable the social cooperation, social learning and the construction of a network of relationships that make culture and its transmission possible [6]. We have argued, in a similar vein, that human consciousness evolved to allow us to share our experiences, to communicate a "shared narrative" on which relationships, social ties, and group cohesion can all be built [7]. We become conscious of those aspects of the world which others reflect on as well, and this applies equally to our internal subjective world [7].…”
Section: Introductionmentioning
confidence: 94%
“…We have argued, in a similar vein, that human consciousness evolved to allow us to share our experiences, to communicate a "shared narrative" on which relationships, social ties, and group cohesion can all be built [7]. We become conscious of those aspects of the world which others reflect on as well, and this applies equally to our internal subjective world [7].…”
Section: Introductionmentioning
confidence: 98%
“…Whereas before puberty the domains of sexuality and aggression were less integrated in the agentive sphere of the individual, their potentiation through pubertal development gradually brings novel possibilities: procreation and potentially causing enduring harm through one’s aggression. This poses an inherent challenge for mentalizing during adolescence, as body-states associated with new experiences of sexual and aggressive arousal remain without fully regulatory second-order representations, unlike other forms of affective arousal stemming from basic emotions which have been mirrored throughout childhood and internalized in the self-regulatory repertoire (Target, 2007; Fonagy, 2008; Fonagy and Allison, 2016; Fonagy and Luyten, 2016). This makes new arousal states in adolescence prone to poorly regulated thought and behavior, especially in situations of stress (Fonagy and Luyten, 2016).…”
Section: Mentalizing As a Moderator Of Psychosis Vulnerabilitymentioning
confidence: 99%
“…According to the definition provided by Peter Fonagy and Anthony Bateman, mentalization refers to "the ability to reflect upon, and to understand one's state of mind" (Bateman & Fonagy, 2012); "to have insight into what one is feeling, and why"; and is assumed to be an important coping skill that is necessary for effective emotional regulation (Bateman & Fonagy, 2012). Previous research has demonstrated that difficulties with emotional regulation are one of the primary characteristics of personality disorders (Fonagy & Allison, 2016;Petersen, Brakoulias, & Langdon, 2016). However, only a few studies have investigated mentalization in affective disorders (Fischer-Kern et al, 2013;Power, Iacoponi, Reynolds, et al, 2007;Santos et al, 2017).…”
mentioning
confidence: 99%